2021
DOI: 10.3389/fcell.2021.686547
|View full text |Cite
|
Sign up to set email alerts
|

RPL19 Is a Prognostic Biomarker and Promotes Tumor Progression in Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most common malignancies, and the therapeutic outcome remains undesirable due to its recurrence and metastasis. Gene dysregulation plays a pivotal role in the occurrence and progression of cancer, and the molecular mechanisms are largely unknown.MethodsThe differentially expressed genes of HCC screened from the GSE39791 dataset were used to conduct weighted gene co-expression network analysis. The selected hub genes were validated in The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To narrow down the number of “candidate” DEGs and determine potential “key” genes for HCC development [ 30 , 31 , 33 , 34 ], a PPI network of 145 DEGs was constructed to visualize the relationships between genes, followed by functional analysis. Based on their connectivity level, the top ten hub genes identified included CCNB1, MAD2L1, CCNA2, AURKA, ZWINT, HMMR, TPX2, EZH2, and OIP5.…”
Section: Discussionmentioning
confidence: 99%
“…To narrow down the number of “candidate” DEGs and determine potential “key” genes for HCC development [ 30 , 31 , 33 , 34 ], a PPI network of 145 DEGs was constructed to visualize the relationships between genes, followed by functional analysis. Based on their connectivity level, the top ten hub genes identified included CCNB1, MAD2L1, CCNA2, AURKA, ZWINT, HMMR, TPX2, EZH2, and OIP5.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the possible role of TRIM55 in HCC, we studied TRIM55 levels in tumor samples and adjacent non-tumor tissues from the GSE84005, 22 GSE64041, 23 GSE39791, 24 GSE36376, 25 and TCGA datasets. The results indicated that TRIM55 expression was upregulated in HCC tissues ( Figure 1A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, while mutants in most ribosomal proteins do not appear to affect aging 94 , orthologs of Rpl1901 (RPL19) are among only four ribosomal proteins shown to affect aging in budding yeast and worms where the loss of RPL19 function extends lifespan 9597 . RPL19 is also among the few ribosomal protein genes that are up-regulated in embryonic stem cells of human blastocysts and hepatocellular carcinoma 98,99 , and post-transcriptional silencing of RPL19 alleviates human prostate cancer by controlling the translation of a subset of transcripts 100 . Ribosomal proteins may affect aging in different ways, e.g.…”
Section: Discussionmentioning
confidence: 99%